1982
DOI: 10.2337/diacare.31.12.1077
|View full text |Cite
|
Sign up to set email alerts
|

Binding, Internalization, and Degradation of Insulin in Vascular Endothelial Cells

Abstract: The interaction of insulin with the vascular endothelium was studied using bovine aortic endothelial cells in monolayer cultures. Confluent cell cultures exhibited specific binding of 125I-insulin to high- and low-affinity cell surface receptor sites. Binding was reversible, saturable, and accompanied by internalization and degradation of the bound hormone in a temperature- and time-dependent manner. Pre-exposure of the cultures to insulin resulted in a time-dependent reduction in the availability of cell surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This finding, which is in accordance with previous studies [9,12], is in line with the concept of a saturable endothelial transport system for insulin delivery. A saturable transcapillary transport with the characteristics of a receptor‐mediated transpinocytotic process under physiological insulin concentrations has been described in vitro [21–23]. These findings were supported by the characterization of a vascular endothelial insulin receptor [24,25].…”
Section: Discussionmentioning
confidence: 85%
“…This finding, which is in accordance with previous studies [9,12], is in line with the concept of a saturable endothelial transport system for insulin delivery. A saturable transcapillary transport with the characteristics of a receptor‐mediated transpinocytotic process under physiological insulin concentrations has been described in vitro [21–23]. These findings were supported by the characterization of a vascular endothelial insulin receptor [24,25].…”
Section: Discussionmentioning
confidence: 85%
“…Insulin binding was studied using a modification of the methods of Kaiser et al [8]. The cells were plated into dishes with DMEM containing 0.5% FBS for 24 hours and incubated at 37℃ with Tris-Hepes binding buffer (50 mM Tris, 50 mM Hepes, 10 mM MgC1 2 , 2 mM EDTA, 10 mM dextrose, 10 mM CaC1 2 , 50 mM NaCl, 5 mM KCl, 0.5% crystalline BSA, pH 7.8) and [ 125 I]-insulin (0.5 µCi/well) for 0, 10, 20, 30, 60, and 90 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Early in vitro studies by King and Johnson [81] and others [90] suggested this was the case. However, in the canine hindlimb [85], the appearance of insulin in lymphatic drainage did not reach saturation point when plasma insulin was raised from high physiological to pharmacological concentrations.…”
Section: Movement Of Insulin Across the Endothelial Lining Of The Micmentioning
confidence: 99%